The discovery of genus Fredegunda Fitton, Shaw & Gauld in China, with description of a new species (Hymenoptera, Ichneumonidae, Pimplinae) - Liu, Jing-Xian; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2013)
The genus Fredegunda Fitton, Shaw & Gauld (Ichneumonidae, Pimplinae) is newly reported both from China and the Ori-ental region. A new species, Fredegunda sinica sp. nov. from Fujian, China is described and illustrated. A key to the known species of Fredegunda is provided.